Enhancing the functional characteristics of sago starch through dual chemical modification by hydroxypropylation and succinylation - Derina Paramitasari; Musa Musa; Okta Nama Putra; Sarah Elisa; Suparman Suparman; Taufik Hidayat; Yanuar Sigit Pramana (Universitas Scientiarum)
Sago starch is a locally abundant starch indigenous of Indonesia. Despite its abundance, it is underutilized and restricted to food and packaging applications due to its limited functional characteristics. The value of native sago starch can be increased through modifications that improve its functionality, such as dual chemical modification. This sophisticated approach is more effective than single modification and makes the starch suitable for wider applications. Our study aimed to determine if dual chemical modification involving hydroxypropylation and succinylation would optimize the functional properties of sago starch. The sago starch was first modified by hydroxypropylation with 7 % (w/w) propylene oxide under alkaline conditions for 3 hours. This process resulted in hydroxypropylated starch with a substitution degree of 0.107. We then subjected the starch to succinylation using succinic anhydride at 1 % to 5 % of the starch weight in an alkaline solution for 2 hours. We achieved optimal functional characteristics of the dual-modified sago starch in the sample modified with 3 % (w/w) of succinic anhydride. The succinyl degree of substitution, water holding capacity, oil holding capacity, swelling power, and solubility of the dual-modified starch were 0.093, 4.16 g g􀀀1, 7.20 g g􀀀1, 34.25 g g􀀀1, and 16:55 %, respectively. We conducted pasting properties analyses, infrared spectroscopy, and morphological structure analysis to determine the changes in the characteristics of the sago starch after hydroxypropylation and succinylation. The dual chemical modification successfully enhanced the functional characteristics of sago starch, particularly, its amphiphilic ability and swelling power. These results warrant further research and development in commercial applications.